Seed storage studies in Mesua ferrea L. a medicinal tree of Indo-Malayan region - Mithun, V; Pradeep, N S; Krishnan, P N (Plant Science Today, 2021)
This paper, deals with testing the storage and viability of the seeds of Mesua ferrea L. in 5 different storage conditions. Seeds of M. ferrea are recalcitrant in nature and lose viability with a short span 8-15 days. Of the different conventional methods tried using the polycarbonate bottle and bags, M. ferrea seeds retained viability for 150 days with a slow moisture loss from the seeds stored in closed polycarbonate bottles at 10 °C. Here, we have standardised a conventional technique whereby the viability of the seeds can be extended to 150-180 days by storing the seeds in polycarbonate bottles at 10 °C.